2002
DOI: 10.1074/jbc.m209128200
|View full text |Cite
|
Sign up to set email alerts
|

Increased Risk of Atherosclerosis by Elevated Plasma Levels of Phospholipid Transfer Protein

Abstract: Plasma phospholipid transfer protein (PLTP) is thought to be involved in the remodeling of high density lipoproteins (HDL), which are atheroprotective. It is also involved in the metabolism of very low density lipoproteins (VLDL). Hence, PLTP is thought to be an important factor in lipoprotein metabolism and the development of atherosclerosis. We have overexpressed PLTP in mice heterozygous for the low density lipoprotein (LDL) receptor, a model for atherosclerosis. We show that increased PLTP activity results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
123
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(139 citation statements)
references
References 43 publications
14
123
2
Order By: Relevance
“…Also in mice with adenovirus-mediated overexpression of PLTP, increased levels of pre-␤-HDL were observed (12,13). In contrast, PLTP deficiency in hyperlipidemic mice models has resulted in decreased atherosclerosis that was explained via the effects on VLDL secretion (41), and strong overexpression of PLTP in mice heterozygous for the LDL receptor has been shown to increase the susceptibility to atherosclerosis (42). However, both the overexpression and gene knockout models are quite extreme conditions, and therefore, depending on the metabolic status, PLTP may display anti-or proatherogenic properties.…”
Section: Discussionmentioning
confidence: 99%
“…Also in mice with adenovirus-mediated overexpression of PLTP, increased levels of pre-␤-HDL were observed (12,13). In contrast, PLTP deficiency in hyperlipidemic mice models has resulted in decreased atherosclerosis that was explained via the effects on VLDL secretion (41), and strong overexpression of PLTP in mice heterozygous for the LDL receptor has been shown to increase the susceptibility to atherosclerosis (42). However, both the overexpression and gene knockout models are quite extreme conditions, and therefore, depending on the metabolic status, PLTP may display anti-or proatherogenic properties.…”
Section: Discussionmentioning
confidence: 99%
“…These include the transfer of phospholipids from triglyceride-rich lipoproteins to high-density lipoproteins (HDL) during lipolysis (Tall et al 1985), the remodeling of HDL-particles (Jauhiainen et al 1993;Tu et al 1993), the stimulation of hepatic very low-density lipoprotein (VLDL) secretion (Jiang et al , 2001Lie et al 2002;van Haperen et al 2002), and the modification of the inflammatory and oxidative state of lipoproteins Jiang et al 2002;Schlitt et al 2005;Yan et al 2004;Yang et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Overexpression of human PLTP in lowdensity lipoprotein receptor (LDLR) deficient mice resulted in a dose-responsive increase in susceptibility to atherosclerosis . Most functions of PLTP are potentially atherogenic: overexpression of human PLTP dose-dependently decreases HDL levels, resulting in a more atherogenic lipoprotein profile (Albers et al 1996;van Haperen et al 2002); overexpression of human PLTP stimulates VLDL secretion by the liver (Lie et al 2002;van Haperen et al 2002); lipoprotein oxidizability increases following adenoviral overexpression of PLTP in atherosclerosis-prone mice (Jiang et al 2002;Yang et al 2003). On the other hand, PLTP has anti-atherogenic potential as well, because it increases the formation of preb-HDL, an HDL subfraction that is a very efficient acceptor of cellular cholesterol and therefore an important mediator in reverse cholesterol transport (Jiang et al 1996;Lie et al 2001;van Haperen et al 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…18,19 In addition, several mouse studies have suggested that genes influencing body fatness in mice reside on chromosome 2 in a region homologous to human chromosome 20q. [20][21][22] Finally, it has been shown that PLPT facilitates the production of triglyceride-rich apoB-containing lipoproteins 23,24 and the transport of lipids from cells, 25 which are central functions of lipid homeostasis. Based on these observations, we hypothesize that PLTP modulates the level of adiposity.…”
Section: Introductionmentioning
confidence: 99%